2020
DOI: 10.3171/2020.7.focus20482
|View full text |Cite
|
Sign up to set email alerts
|

Impact of frailty on surgery for glioblastoma: a critical evaluation of patient outcomes and caregivers’ perceptions in a developing country

Abstract: OBJECTIVEThe authors aimed to evaluate the impact of age and frailty on the surgical outcomes of patients with glioblastoma (GBM) and to assess caregivers’ perceptions regarding postdischarge care and challenges faced in the developing country of India.METHODSThis was a retrospective study of patients with histopathologically proven GBM from 2009 to 2018. Data regarding the clinical and radiological characteristics as well as surgical outcomes were collected from the institute’s electronic database. Taking Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…A systematic review of the literature on ASDH in the elderly [ 33 ] identified the presence of comorbidities to influence the outcome but also evinced the lack of literature objectively assessing comorbidities and frailty with validated instruments. While the evidence is only beginning to emerge on the importance of frailty assessment in CSDH, recent studies have illustrated how it can aid clinicians in prognostication in other neurosurgical pathologies, including glioblastoma [ 34 ], meningioma [ 35 ], and other primary central nervous system tumors [ 36 ]. Thus, the inclusion of this additional criterion into prognostication tools in CSDH appears warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the literature on ASDH in the elderly [ 33 ] identified the presence of comorbidities to influence the outcome but also evinced the lack of literature objectively assessing comorbidities and frailty with validated instruments. While the evidence is only beginning to emerge on the importance of frailty assessment in CSDH, recent studies have illustrated how it can aid clinicians in prognostication in other neurosurgical pathologies, including glioblastoma [ 34 ], meningioma [ 35 ], and other primary central nervous system tumors [ 36 ]. Thus, the inclusion of this additional criterion into prognostication tools in CSDH appears warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Reported thresholds in mFI-11 scores differed by study and were similarly reported as either integers or as fractions. Cloney and Katiyar categorized patients into three integer-based categories: low frailty (0) vs. moderate frailty (1-2) vs. high frailty (≥ 3) [14,24]. Schneider used three similar categories reported as fractions based on a denominator of 11 (least-frail (0-0.08) vs. moderately-frail (0.09-0.26) vs. frailest (≥ 0.27)) [27].…”
Section: Frailty Instruments Studiedmentioning
confidence: 99%
“…Frailty status as ascertained by the mFI-5 was associated with mortality, complications, LOS, charges, discharge disposition, operation time, and readmissions [15, 17-20, 22, 26]. Frailty status using the mFI-11 was associated with in-hospital mortality, overall survival, complications, LOS, charges, discharge disposition, end of life care needs, and reoperation rates [13,14,22,24,25,27,30,31]. Frailty using the JHACG tool was associated with mortality, complications, reoperation rates, LOS, charges, costs, discharge disposition, and readmissions [11,12,28,29].…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…At the time of discharge, the mean KPS was 85 (range 30-100), mean ECOG was two (range 0-4). On admission, geriatric patients with glioblastoma had a median GFI of five (range 1-11) and a median G8 score of 12 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). According to GFI, 43 (41.34%) geriatric patients with glioblastoma showed no signs of frailty, 51 (49.04%) according to the G8 Questionnaire.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…A growing body of evidence suggests that frailty is a more appropriate predictor of surgical outcome, post-operative complications, and impaired overall survival than chronological age (11). Although frailty screening tests offer assessment tools to stratify geriatric patients and identify those at risk for a detrimental outcome, they are not commonly used in informing surgical decisions (12).…”
Section: Introductionmentioning
confidence: 99%